2000
DOI: 10.1038/sj.bmt.1702479
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, randomized, parallel-group study on the efficacy and safety of oral granisetron and oral ondansetron in the prophylaxis of nausea and vomiting in patients receiving hyperfractionated total body irradiation

Abstract: Summary:The efficacy and safety of granisetron and ondansetron for the prophylaxis of nausea and vomiting resulting from hyperfractionated total body irradiation (TBI) were assessed. Thirty-four patients randomly received double-blind, oral granisetron (2 mg, 1 h before first daily fraction of radiation) or ondansetron (8 mg, 1.5 h prior to each fraction of TBI). Ninety patients who received the same TBI regimen prior to bone marrow transplantation (BMT), but no 5-HT 3 -receptor antagonist, were identified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…13 Patients in the granisetron group had a 33.3% control of vomiting versus 26.7% control in the ondansetron group. Their conclusion was that more optimal therapy was needed.…”
Section: Resultsmentioning
confidence: 99%
“…13 Patients in the granisetron group had a 33.3% control of vomiting versus 26.7% control in the ondansetron group. Their conclusion was that more optimal therapy was needed.…”
Section: Resultsmentioning
confidence: 99%
“…19 For patients receiving high-dose chemotherapy or chemo/ radiotherapy regimens in association with hematopoietic stem cell support, a number of studies suggest that antiemetic control may be a greater challenge in this setting. 17,[20][21][22][23][24][25] In the current prospective trial, we have clearly demonstrated that despite the use of standard prophylactic treatments, antiemetic control is indeed suboptimal for patients receiving allogeneic or autologous hematopoietic stem cell transplants and appears to be inferior to the results obtained with standard-dose chemotherapy. Limitations of the study include the diverse conditioning regimens, antiemetic treatments, and small sample size.…”
Section: Discussionmentioning
confidence: 91%
“…A retrospective study of ondansetron in the ED reported that 38% (n = 12,620) of prescriptions were for reasons other than gastroenteritis in the ED. 15 Other indications of ondansetron are post-operativem, [44][45][46] chemotherapy, radiotherapy, 47,48 sedation, 49 or during pregnancy. 50 Recently, ondansetron has been prescribed for brain-related diseases like obsessive-compulsive disorders 51 or drug/alcohol addictions, [52][53][54] suggesting that it may influence other symptoms than vomiting.…”
Section: Discussionmentioning
confidence: 99%